0789 Mask Magnets May Interact with Pacemakers and Implantable Cardioverter-Defibrillators. (25th May 2022) - Ruoff, Chad; Tashman, Yasemin; Miller, Bernie; Houser, Ryan; Cheema, Kamal; Haley, Caitlin; Petersen, Ann; Lizak, Matthew; Goswami, Umesh; Lizak, Trevor; Krahn, Lois; Srivathsan, Komandoor
Abstract: Introduction: Placing a magnet over a Permanent Pacemaker (PPM) or Implanted Cardioverter-Defibrillator (ICD) may cause the device to pace asynchronously or inhibit tachyarrhythmia detection, respectively, potentially preventing delivery of electrical shocks. Manufacturers for masks used with positive airway pressure devices have started using magnets in place of more traditional headgear clips to connect the headgear to mask. Mask manufactures do not list presence of a PPM/ICD as a contraindication to use of a mask with magnet but do recommend keeping the mask some distance away from PPM/ICD. A published case series describes two patients with magnet response events captured during PPM/ICD interrogation that correlated with nightly use of CPAP. The authors were able to replicate the response by placing the mask with magnet directly over the patient's pulse generate site. Although we advise all patients with implanted device to avoid use of masks with magnets, select patients refuse to stop using mask with magnets regardless of our policy. We, therefore, started offering these patients referral for PPM/ICD interrogation to evaluate for an interaction between mask with magnet and PPM/ICD as next best alternative. Methods: We retrospectively reviewed all patients (n=10) referred for routine PPM/ICD interrogation to test whether the mask with magnet interacted with PPM/ICD when mask on face as during normal use (i.e., simulated normal use) or magnetic area of mask placed directly over the PPM/ICD (i.e., direct contact). Results: Although no interaction was detected in any patient (n=10) with simulated normal use (0 %), one interaction was documented with direct contact (10 %). Conclusion: Although simulated normal use of masks with magnets did not demonstrate any interactions, it is concerning that one patient (10 % of patients) demonstrated an interaction with direct contact of magnetic area of mask over the PPM/ICD. It is not uncommon for patients to remove a mask during the night while sleeping. This preliminary data along with the published case series calls for further research and increased awareness of this potential interaction for both sleep and cardiac health care providers. Support (If Any): None